IDENTIFYING ENGLISH LANGUAGE CLASSROOM ANXIETY OF STUDENTS OF INTERNATIONAL RELATIONS - Zarina Markova; Teodora Yaneva (Studies in Linguistics, Culture, and FLT, 2020)
The article presents the findings of a small-scale study of the English language anxiety of students of International Relations at South-West University “Neofit Rilski”, Blagoevgrad. Data were collected via the Foreign Language Classroom Anxiety Scale (FLCAS). The survey results suggest that speaking and test taking are the aspects of English language learning that provoke most anxiety in the surveyed group. Additionally, there are indications that respondents fear their peers’ negative evaluation. Changes in the teaching practice are suggested that might reduce the level of students’ English language classroom anxiety.